Utilization of Open Video Repository-Assisted Inquiry Based Learning (IBL) on Computer Network Basics Course : Its Effect on Student Interest and Learning Outcomes - Fajarwati, Aprilia; Basori; Hatta, Puspanda (Politeknik NEST, 2024)
Learning models that are not suitable in learning can make students' interests and learning outcomes less than optimal. Therefore, educators must make the selection of the right learning model. The difference in the influence of Inquiry Based Learning assisted by open video repository on student interests and learning outcomes is the purpose of this study. The research design used was a pseudo-experimental method with a pretest posttest control group design. The class that was given the treatment of using the Inquiry Based Learning learning model assisted by the Open Video Repository was an experimental class, while the control class used the Discovery Learning learning model. The population and samples used were class TJKT 1 as an experimental class and class TJKT 2 as a control class. The data collection technique uses a questionnaire instrument and the value of student learning outcomes which is then tested using SPSS. After conducting data analysis, data were obtained (1) sig(2-tailed) values of 0.047 < 0.05 (2) sig(2-tailed) values of 0.000 < 0.05 (3) student learning interest gain tests in experimental classes 0.32 greater than control classes 0.16 (4) gain tests of student learning outcomes in experimental classes 0.68 were greater than control classes 0.44. It can be concluded that in the use of the Inquiry Based Learning learning model assisted by the Open Video Repository there is a significant influence and has increased effectiveness compared to those who do not use the model on student interest and learning outcomes in the subject basics of Computer Network Engineering and Telecommunications.